2016
DOI: 10.1016/j.redox.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Oxalomalate reduces expression and secretion of vascular endothelial growth factor in the retinal pigment epithelium and inhibits angiogenesis: Implications for age-related macular degeneration

Abstract: Clinical and experimental observations indicate a critical role for vascular endothelial growth factor (VEGF), secreted by the retinal pigment epithelium (RPE), in pathological angiogenesis and the development of choroidal neovascularization (CNV) in age-related macular degeneration (AMD). RPE-mediated VEGF expression, leading to angiogenesis, is a major signaling mechanism underlying ocular neovascular disease. Inhibiting this signaling pathway with a therapeutic molecule is a promising anti-angiogenic strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…In previous studies, low oxygen tension within spheroids is shown to play a key role in tumor progression and promotion of angiogenetic cytokines like stromal cell derived factor (SDF), IL-1β, TNF-α and vascular endothelial growth factor (VEGF). 57–60 In addition, the oxygenation is also found to be improved by influence of endothelial cells, 61 which agrees with the observation in the experiments.…”
Section: Resultssupporting
confidence: 86%
“…In previous studies, low oxygen tension within spheroids is shown to play a key role in tumor progression and promotion of angiogenetic cytokines like stromal cell derived factor (SDF), IL-1β, TNF-α and vascular endothelial growth factor (VEGF). 57–60 In addition, the oxygenation is also found to be improved by influence of endothelial cells, 61 which agrees with the observation in the experiments.…”
Section: Resultssupporting
confidence: 86%
“…VEGF may promote cell proliferation, differentiation, migration and movement by increasing the permeability of blood vessels and degradation of extracellular matrix (35). VEGF upregulation may promote blood vessel growth, facilitate inflammatory factors secretion and aggravate inflammation, leading to damage of vascular integrity (36). In the present study, a significant reduction in the expression levels of VEGF mRNA and protein in RPE cells was observed following IL-10 treatment, which suggested that IL-10 may inhibit angiogenesis through the downregulation of VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…RPE cells are highly metabolically active cells that are located in the retina and play a vital role in maintaining normal visual function. Hence, RPE cells are vulnerable to oxidative stress [ 7 , 39 ]. In addition, sunlight is one of the causes for ROS production that can damage RPE cells [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%